2005
DOI: 10.1074/jbc.m414348200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Carbonic Anhydrases from Mycobacterium tuberculosis

Abstract: Carbonic anhydrases catalyze the reversible hydration of carbon dioxide to form bicarbonate. This activity is universally required for fatty acid biosynthesis as well as for the production of a number of small molecules, pH homeostasis, and other functions. At least three different carbonic anhydrase families are known to exist, of which the ␣-class found in humans has been studied in most detail. In the present work, we describe the structures of two of the three ␤-class carbonic anhydrases that have been ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
178
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(182 citation statements)
references
References 32 publications
3
178
0
1
Order By: Relevance
“…In contrast, type II b-CAs are catalytically active only at a pH 8 and higher where they adopt a functional active site configuration like that of type I. In fact, below pH 8 they are conformationally selfinactivated by the addition of a fourth amino acid (an Asp residue) which coordinates to the Zn(II) ion as the fourth ligand, and displacing the zinc bound solvent 39,52 . At pH48, the Asp copordinated to Zn(II) makes a salt pair interaction with a conserved Arg residue, which ''opens'' the active site in the sense that a water molecule/hydroxide ion takes the place of the Asp residue, generating thus the nucleophile responsible for the catalytic activity of these enzymes 39,48-52 .…”
Section: Catalytic Activity Of B13-camentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, type II b-CAs are catalytically active only at a pH 8 and higher where they adopt a functional active site configuration like that of type I. In fact, below pH 8 they are conformationally selfinactivated by the addition of a fourth amino acid (an Asp residue) which coordinates to the Zn(II) ion as the fourth ligand, and displacing the zinc bound solvent 39,52 . At pH48, the Asp copordinated to Zn(II) makes a salt pair interaction with a conserved Arg residue, which ''opens'' the active site in the sense that a water molecule/hydroxide ion takes the place of the Asp residue, generating thus the nucleophile responsible for the catalytic activity of these enzymes 39,48-52 .…”
Section: Catalytic Activity Of B13-camentioning
confidence: 99%
“…A conserved domain database (CDD) (http://www.ncbi.nlm.nih.gov/Structure/cdd/ wrpsb.cgi) search of Enterobacter sp. B13 can sequences showed that the active and ion binding site residues of B13-CA are well conserved, as in all b-CAs investigated in detail, such as among others the enzymes from H. influenzae, Citrobacter freundii, Pseudomonas aeruginosa, Synechococcus elongatus, Brucella suis, E. coli, Methanothermobacter thermautotrophicus, Salmonella enterica, Pectobacterium carotovorum, Helicobacter pylori, Porphyromonas gingivalis, Vibrio cholerae, Streptococcus pneumoniae, S. mutans and Mycobacterium tuberculosis Rv1284 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Figure 4). …”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…For these enzymes, no water coordinated to the metal ion is present at pH values <8, as shown in an excellent crystallographic work from Jones' group on the mycobacterial enzymes Rv3558c and Rv1284 13 . However, at pH values >8, a conserved Arg residue in all β-CAs investigated thus far (belonging to a so-called catalytic dyad) makes a salt bridge with the Asp coordinated to Zn(II), liberating the fourth Zn(II) coordination position, which is then occupied by an incoming water molecule/hydroxide ion 12,13 . The substrate CO 2 was found bound (for the α-class enzymes 10 ) in a hydrophobic pocket nearby the Zn(II) ion, defined among others by residues Val121, Val143 and Leu198 (in the human [h] isoform hCA II, for which the x-ray crystal structure in complex with CO 2 was reported in a seminal paper by McKenna's group 10 ), as represented in Scheme 1B.…”
Section: Introductionmentioning
confidence: 99%
“…The metal ion ligands are three His residues in α-, γ-and δ-CAs or one His and two Cys residues in β-and ζ-CAs [1][2][3][4][5][6][7][8][9] . Some β-class enzymes have four protein zinc ligands, that is, one His, two Cys and one Asp coordinated to Zn(II) 12 . For these enzymes, no water coordinated to the metal ion is present at pH values <8, as shown in an excellent crystallographic work from Jones' group on the mycobacterial enzymes Rv3558c and Rv1284 13 .…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes, so called mtCA 1, 2 and 3 and encoded, respectively, by the genes Rv1284, Rv3588c and Rv3273 [1][2][3][4][5][6] . Indeed, the CA superfamily of enzymes comprises the a-, b-, g-, -and z-CA classes, all of which are generally efficient catalysts for the reversible interconversion between carbon dioxide and bicarbonate (CO 2 þ H 2 O Ð HCO 3 -þ H þ ) 7 .…”
Section: Introductionmentioning
confidence: 99%